Electronic structure and optical properties of triangular GaAs/AlGaAs quantum dots: Exciton and impurity states (2016)
Electronic structure and optical properties in equilateral triangular GaAs/Al0.3Ga0.7As quantum dots are studied extensively. The effects of donor and acceptor impurity atoms positioned in the orthocenter of the triangle, as well as of the external DC electric field are taken into account. Binding energies of the impurity, exciton energies, interband photoluminescence peak positions as well as linear and non-linear optical properties in THz range caused by transitions between excitonic states are calculated and discussed. © 2015 Elsevier B.V. All rights reserved.